2014
DOI: 10.1159/000430474
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Mechanical Thrombectomy Using Stent Retrievers in the Endovascular Treatment of Acute Ischaemic Stroke: A Systematic Review

Abstract: Background:The treatment of choice for acute ischaemic stroke is the intravenous administration of recombinant tissue plasminogen activator within 3-4.5 h of symptom onset. However, the use of a thrombolytic would be limited by its narrow therapeutic window and contraindications. As a result, in recent years, techniques such as mechanical thrombectomy have emerged, which employ thrombus retrieval devices, such as stent retrievers (Solitaire TM , Trevo ® or Revive TM ), whose safety and efficacy in the endovasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 48 publications
(112 reference statements)
0
17
0
Order By: Relevance
“…In 2014 and from 2016 to 2018, the success rate at our center is in the range of 83-86%. Recent literature comes to similar success rates of around 80-89% [6,16], while older reviews indicate success rates of 80% [17].…”
Section: Discussionmentioning
confidence: 99%
“…In 2014 and from 2016 to 2018, the success rate at our center is in the range of 83-86%. Recent literature comes to similar success rates of around 80-89% [6,16], while older reviews indicate success rates of 80% [17].…”
Section: Discussionmentioning
confidence: 99%
“…These previous reviews are limited by the use of nonrandomized data and thus may be affected by confounding by indication and other variables. Another recent systematic review and metaanalysis 17 included only 2 RCTs comparing stent retrievers with the first-generation Merci coil retriever and none of the recently published stent-retriever RCTs. Although data were pooled in a commentary written by Goyal and Menon 18 that examined the 5 acute endovascular RCTs published in 2015, their meta-analysis was conducted outside the context of a systematic review.…”
Section: Discussionmentioning
confidence: 99%
“…The second-generation stent retrievers Solitaire and Trevo are self-expanding stents that trap the thrombus against the vessel wall and can be retrieved via catheter 9–11. A meta-analysis of 17 primary studies showed that stent retrievers (both Trevo and Solitaire) have superior revascularization rates and clinical outcomes with a similar safety profile to the Merci device 12. Additionally, a meta-analysis of 19 studies comparing Trevo and Solitaire devices showed similar efficacy and safety except for higher mortality rates with the Trevo device 13…”
Section: Introductionmentioning
confidence: 99%